Les doreurs de Barcelone : un métier face à l’évolution du goût et des pratiques (1770-1834) - Julien Lugand (Les Cahiers de Framespa)
In Barcelona, in the second half of the 18th century, several decrees and royal orders had a profound effect on the gilders’ profession. Forced to adapt to the liberalisation of practices and the slow disappearance of gilding-polychromy, their activity evolved towards decorative painting, of which they tried to obtain a monopoly.